The geography of international terrorism an introduction to spaces and places of violent non-state groups - Medina, Richard M.; Hepner, George F. (CRC Press, 2013)
Providing the perspective required to understand and anticipate terrorism, this book presents an accessible, cross-disciplinary approach to managing terrorism on a global scale.